2023
DOI: 10.1177/09720634231153226
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Inequality and Determinants of Catastrophic Health Expenditure in India

Abstract: This study tries to estimate the incidence, intensity and inequality of Catastrophic Health Expenditure in India and its determinants using unit-level data from the four consecutive surveys of NSSO on ‘Healthcare Consumption and Morbidity’ spread across a 23-year period. For CHE incidence, a 10% threshold level of household consumption expenditure is considered. Additionally, socio-economic determinants of CHE were identified using multivariate logistic regression. Study reveals that the demand for healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Furthermore, evidence on hospitalization from countries such as Argentina, China, India, and Tanzania also revealed the disproportionate impact of CHE on the poor (21). Although there is some literature on the impact of socioeconomic inequalities on the incidence of catastrophic payments in the Indian context (22)(23)(24), the evidence is rather exiguous and does not commensurate with the policy implications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, evidence on hospitalization from countries such as Argentina, China, India, and Tanzania also revealed the disproportionate impact of CHE on the poor (21). Although there is some literature on the impact of socioeconomic inequalities on the incidence of catastrophic payments in the Indian context (22)(23)(24), the evidence is rather exiguous and does not commensurate with the policy implications.…”
Section: Introductionmentioning
confidence: 99%
“…While the country has seen a decrease in CHE over the past decade, there has been a simultaneous rise in associated inequality (Mohanty & Dwivedi, 2021). A recent study by Gaddam and Rao (2023) revealed that despite a decline in catastrophic events, there has been a noticeable upsurge in the unequal distribution of the burdens these events impose on affected populations. As we move closer to universal healthcare, defining a fair financial contribution for healthcare service users is a key policy challenge (Moradi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%